Food addiction in Bulimia Nervosa: Analysis of body composition, psychological and problematic foods profile - Munguía, Lucero; Camacho-Barcia, Lucía; Gaspar-Pérez, Anahí; Granero, Roser; Galiana, Carla; Jiménez-Murcia, Susana; Dieguez, Carlos; Gearhardt, Ashley Nicole; Fernández-Aranda, Fernando (Frontiers in Psychiatry, 2022)
INTRODUCTION: Food Addiction (FA) has been related with eating disorders (ED), especially Bulimia Nervosa (BN). BN + FA may have different physical characteristics than patients with BN without the comorbidity, such as body mass index (BMI) or body composition, and psychological as emotion regulation. However, the relationship between psychological and physical aspects, connected by problematic food and its influence on body composition, has been barely studied. Therefore, the aims of the present study are: AIMS: a) to explore the differences in body composition between FA positive (FA+) and negative (FA-) in women with BN; b) to identify problematic relationship with certain food types, according with the foods mentioned in the YFAS scale questionnaire, between FA + and FA - patients; c) to know the psychological characteristic differences between FA + and FA - patients, considering emotion regulation, personality traits and general psychopathological state; d) to identify the relationship between physical and psychological traits, and the identified problematic foods, in patients with BN and FA. METHODOLOGY: N=81 BN women patients, with a mean age of 29.73 years ± 9.80 SD, who completed the questionnaires: Yale Food Addiction Scale V 1.0 (YFAS 1.0), Eating Disorder Inventory-2 (EDI-2), Symptom Checklist-90 Items-Revised (SCL-90-R), and Difficulties in Emotion Regulation Strategies (DERS). YFAS problematic foods were grouped considering their principal nutrients sources. Body composition and difference in metabolic age was determined using bioimpedance analyser. RESULTS: The 88% of patients with BN presented FA+. Patients with BN who were FA+ self-reported more problematic relationships with sweets and starches. Also presented higher emotion regulation difficulties, general psychopathology and eating symptomatology severity, than those without FA. Finally, emotional regulation difficulties were positively associated with higher eating disorder symptomatology and more types of foods self-reported as problematic, which increased indirectly fat mass. CONCLUSIONS: The results suggest that BN+FA presented more eating and psychopathology symptomatology and higher problems with specific food types. As well, the path analysis emphasized that emotion regulation difficulties might be related with problematic food relationship in BN, impacting over the ED severity. IMPLICATIONS: The results may impact the development of precise therapies for patients with BN+FA.